The Transformational Leadership of the School Principal and Its Influence on the Teacher Learning Culture - Komara, Endang; Hidayat, Hidayat; Fauzi, Ikka Kartika Abbas; Juwarto, Juwarto; Haryono, Wasis; Yusuf, Yusuf; Sartono, Sartono (Al-Qalam Institue, 2025)
This study aims to deeply explore the influence of transformational leadership practiced by the school principal on the development of a learning culture and the reinforcement of teachers’ learning motivation at SMAN 112 Jakarta. Employing a qualitative approach with a case study design, the research provides a contextualized understanding of educational leadership dynamics at the secondary school level. Data were collected through a triangulation strategy comprising in-depth interviews, non-participant observations, and institutional document analysis, involving the principal, vice principals, and teaching staff. Data analysis was conducted interactively through systematic and iterative processes of data reduction, data display, and conclusion drawing and verification. The findings reveal that the principal optimally implements all dimensions of transformational leadership, including idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These leadership practices have successfully fostered a teacher learning culture that is collaborative, reflective, innovative, and oriented toward ongoing professional development. Teachers demonstrated a high degree of enthusiasm in enhancing their competencies, sharing best practices, and initiating instructional innovations. The study affirms that transformational leadership constitutes a critical variable contributing to the improvement of instructional quality and the strengthening of teachers’ professional capacities. The practical implications of this study offer strategic recommendations for developing effective educational leadership models within secondary education institutions.